Avaliação da segurança e da atividade imunomoduladora dos extratos de Uncaria tomenosa e Uncaria guianensis sobre a patogenia dos Diabetes Melito autoimune induzido pela estreptozotocina - Domingues, Alexandre [UNESP] (2011)
Uncaria tomentosa (Willd.) DC (Rubiaceae) is a large woody vine that is native to the Amazon and Central American rainforests and is widely used in traditional medicine for its immunomodulatory and anti-inflammatory activities. The present work used in vivo immunotoxic and in vitro immunomodulatory experiments to investigate the effects of a pentacyclic oxindole alkaloid extract from U. tomentosa bark on lymphocyte phenotype, Th1/Th2 cytokine production, cellular proliferation and cytotoxicity. For the in vivo immunotoxicity testing, BALB/c male mice were treated once a day with 125, 500 or 1250 mg/kg of U. tomentosa extract for 28 days. For the in vitro protocol, lymphocytes were cultured with 10 to 500 μL/mL of the extract for 48 h. The extract increased the cellularity of splenic white pulp and the thymic medulla and increased the number of T helper lymphocytes and B lymphocytes. Also, a large stimulatory effect on lymphocyte viability was observed. However, mitogen-induced T lymphocyte proliferation was significantly inhibited at higher concentrations of U. tomentosa extract. Furthermore, an immunological polarization toward a Th2 cytokine profile was observed. These results suggest that the U. tomentosa aqueous-ethanol extract was not immunotoxic to mice and was able to modulate distinct patterns of the immune system in a dose-dependent manner